What makes employees stay?: Exploring the dimensions in context of urban-centric business process outsourcing industry in India - Sengupta, Santoshi; Dev, Santosh (Strategic outsourcing, 2013)
Purpose - Business process outsourcing (BPO) industry in India is progressing with an unparalleled velocity. Although, much research has taken place time and again elaborating on attrition, which is a menace to this industry, not much of work has been done on retention. The present study aims to explore the dimensions of retention in a comprehensive manner. The paper identifies the main factors that lead to retention, compares these dimensions across various demographic characteristics and develops a regression model to find out the contribution of the factors to the long term sustenance of employees in a BPO. Design/methodology/approach - A questionnaire was completed by 500 BPO employees located in the National Capital region of India. It measured their perception towards the importance of factors that are responsible for their sustenance in the organization. Data was analyzed using tests like factor analysis, descriptive stats, correlation and regression. Findings - Four major dimensions of retention were extracted. Of the four job-related dimensions and five personal characteristics, intrinsic motivation factor, employee involvement factor, age and education are the primary determinants of employee retention. It was also found that there is a difference in perception of BPO employees towards the importance of these job-related retention dimensions. Research limitations/implications - Due to selection of only a few facets of job characteristics, and limited geographical area of data collection, generalization of the study findings is limited. Future replication studies with more job characteristics and wider geographical selection in other related subject areas are also recommended. Practical implications - Research findings will contribute to the body of knowledge in the BPO literature on employee retention programs and educate BPO employers on the organizational benefits associated with loyal, committed workers. Study implications will contribute towards industry's continual pursuit for growth, prosperity and profitability. Originality/value - The present study explores novel dimensions of employee retention and makes a major contribution to the relative influence of job and personal characteristics in the BPO industry.